Knitting Human Rights Values and the Rule of Law in Creating a Human Rights State - Ousu Mendy; Gregorius Sri Nurhartanto; Musa Sarjo (Decova Law Journal, 2025)
A human rights state adheres to human rights values, guided by the principles of the rule of law. There is no rule of law in a society where human rights are not valued. For a legal entity to be recognised as a human rights state, its ideals of human rights as a component of the rule of law must be viewed not only from an intellectual squint of ecumenical values but must also demonstrate how they relate to other key elements of states in ways that depict the principles and values of statehood. Therefore, this research establishes the relations between the values of human rights and the rule of law in building a human rights state. Establishing a relationship between these two sets of ideals, from human rights and constitutional perspectives, will help in amalgamating divergent views that uphold human rights as a practice. The doctrinal research method is employed in this study through the use of scholarly articles, books, and other relevant materials. So, while human rights standards are developed to provide adequate protection, their implementation requires certain structures of the rule of law. Without this, it is unlikely that human rights can be realised. The rule of law, administration of justice and democratic structures are key components in creating a human rights state. The positive development of human rights depends on the creation of certain state institutions and laws, and the implementation of state policies is ensured by an effective legal framework. Internationally recognised human rights also impose restraints on states and retrain them from taking any measures. These result in the violation of a given right through either their organs or agents. Therefore, there should be an increased role for non-legal measures and other non-state actors in the domestic implementation of human rights.